Fire blight (Erwinia amylovora) susceptibility of old Hungarian apple cultivars - Tóth, M.; Honty, K.; Hevesi, M. (International Journal of Horticultural Science, 2005)
The aim of the Hungarian apple breeding program started in the Department of Fruit Science was to find resistant apple cultivars against major diseases (scab, powdery mildew, fire blight). The outbreak of fire blight (Erwinia amylovora) in 1996 motivated us to search new resistant sources principally from old traditional apple cultivars. First of all, cultivars have been gathered since 1997 from Carpathia (Visk) and evaluated between 2001 and 2003. In this recent study evaluation of resistance of old Hungarian genotypes to fire blight collected from the English National Fruit Collection (Brogdale, Faversham) is presented. 13 old Hungarian apple cultivars in 2002, and 38 genotypes in 2005 have been evaluated. We used `Idared’ and ’Jonathan M41’ as susceptible controls and ’Liberty’ and ’Remo’ as resistant ones. Shoots of two-year-old potted plants were inoculated with a mixture of virulent E. amylovora isolates (Ea2, Ea60, Ea67) at a concentration of 5 x 108 cells/ml. Resistance of apple cultivars was evaluated weekly, four times after inoculation by disease severity of symptoms. Numbers of bacterial colonies in 1 cm length shoot were determined in the fourth week after infection. 8 cultivars in 2002 and 9 cultivars in 2005 displayed notable resistance to fire blight based on one-year data. Based on the coincident data of both years, out of the cultivars collected also from Carpathia ‘Pónyik’, and `Sikulai’ were found to be resistant and gene sources additional old Hungarian valuable apple genotypes could be selected: `Szabadkai szercsika’ and `Tordai piros !davit’. The cultivar `Szemes alma’ originated from Visk has proved to be recurrently resistant. The number of bacterial cells in shoots of the investigated cultivars correlated with the severity of symptoms. With this method, which was introduced by us earlier, we can screen cultivars displaying weak visible symptoms, which cannot be proposed as a source of resistance because of their latent infection.